Epidemiology of SARS-CoV-2 infection among staff and students in a cohort of English primary and secondary schools during 2020-2021 - James R. Hargreaves; Sinéad M. Langan; William E. Oswald; Katherine E. Halliday; Joanna Sturgess; Jody Phelan; Patrick Nguipdop-Djomo; Benjamin Ford; Elizabeth Allen; Neisha Sundaram; Georgina Ireland; John Poh; et al. (Elsevier, 2022)
Summary: Background: There remains uncertainty about the epidemiology of SARS-CoV-2 among school students and staff and the extent to which non-pharmaceutical-interventions reduce the risk of school settings. Methods: We conducted an open cohort study in a sample of 59 primary and 97 secondary schools in 15 English local authority areas that were implementing government guidance to schools open during the pandemic. We estimated SARS-CoV-2 infection prevalence among those attending school, antibody prevalence, and antibody negative to positive conversion rates in staff and students over the school year (November 2020-July 2021). Findings: 22,585 staff and students participated. SARS-CoV-2 infection prevalence among those attending school was highest during the first two rounds of testing in the autumn term, ranging from 0.7% (95% CI 0.2, 1.2) among primary staff in November 2020 to 1.6% (95% CI 0.9, 2.3) among secondary staff in December 2020. Antibody conversion rates were highest in the autumn term. Infection patterns were similar between staff and students, and between primary and secondary schools. The prevalence of nucleoprotein antibodies increased over the year and was lower among students than staff. SARS-CoV-2 infection prevalence in the North-West region was lower among secondary students attending school on normal school days than the regional estimate for secondary school-age children. Interpretation: SARS-CoV-2 infection prevalence in staff and students attending school varied with local community infection rates. Non-pharmaceutical interventions intended to prevent infected individuals attending school may have partially reduced the prevalence of infection among those on the school site. Funding: UK Department of Health and Social Care.